The Determinants of Dividend Payments in UK: An Empirical Analysis - An, Mo (2012)
Abstract This dissertation is to investigate the determinants of dividend payments in UK. In this study, 50 firms listed in UKfrom five industries are selected to use as sample dataset between 2005 and 2011. Six determinants (profitability, firm size, liquidity, investment opportunity, and leverage and asset structure) are chose based on the previous studies and theories. Moreover, six hypotheses of these determinants have been established and tested by using regression model. Empirical findings concluded that the profitability, firm size, leverage and asset structure are strongly and significantly positive to dividend payments. Investment opportunity is the only one determinant that has an inverse correlation with dividend payments. In addition, there is no association between liquidity and dividend distribution. These results indicated some important issues. Firstly, firms‟ dividend payment was proved that they highly depend on their profitability. Secondly, firms prefer to pay higher dividends to mitigate the agency problems. Thirdly, investment opportunity has negative effect on dividend payment. But, this conclusion cannot represent that firms cut dividends to support their investments. The positive relationship between leverage and dividend distribution can explain that firms borrow more debts to pay dividends and finance their investment. Thus, they can use higher dividend payments to convey information to the outsiders.